Beach morphology and nearshore processes on a sheltered beach — The case of Napatree Beach, Rhode Island - Sakalowsky, Peter P. (Marine Geology, 1975)
On the north side of Napatree Beach, short-term changes of the beach-face within the intertidal zone were studied to determine those processes most influential in causing change where nearshore processes are low in magnitude and beach changes are subtle. The data were subjected to multiple linear correlation and stepwise multiple-regression analyses. Tide level accounts for 41% of the explained variation for the relationship between the processes and beach height. Tide level is the only significant element effecting change in the beach profile. Wave height has no influence on changes in beach morphology. Significant results of beach energy associations have been obtained where low-amplitude nearshore processes are present even when beach changes are subtle. © 1975.
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00131 tex.type: [object Object]
Keywords: dept.egm

Maritime Law-Enforcement - Maritime Sovereignty and Continental-Shelf of Venezuela Within International Context of Maritime Law - Spanish - Nweihed,kg - Glassner, MI (Journal of Developing Areas, 1975)
tex.unique-id: ISI:A1975AS03300023
Keywords: dept.egm; ⛔ No DOI found

Climatology - Fundamentals and Applications - Mather,jr - Sakalowsky, PP (Professional Geographer, 1975)
tex.unique-id: ISI:A1975BH50900027
Keywords: dept.egm; ⛔ No DOI found